A High-Precision Calculation Method for Internal Trajectory of Underwater Weapon Launch - Chun YANG; Kaifu LI; Weibin CHEN; Lutian LI; Yinlong LI (水下无人系统学报)
A high-precision calculation method for internal trajectory was proposed for the pneumatic launch system of underwater weapons. The method combined high-precision theoretical derivation with computational fluid mechanics slip technique and used the fourth-order Runge-Kutta method to solve the high-pressure gas domain during the launch process. The sliding grid was used to simulate the single degree of freedom weapon launch in the water area, so as to realize the high-precision calculation of internal trajectory, which could make up for the defects of large theoretical calculation error and high cost of fluid simulation. Through comparison with the test data, it can be seen that the average error of the discharge velocity of the weapon and the average error of the cutoff pressure of the posterior cavity obtained by this method are 5.6% and 4.0%, which proves the accuracy of this method.